A Theory of Tasteful and Distasteful Transactions. (11th January 2018) - Khalil, Elias L.; Marciano, Alain
Summary: This paper develops a theory of tasteful and distasteful exchanges based on rational choice. By making reference to existing literature, we first differentiate repugnant from tasteful/distasteful transactions and bring up the additional consideration of the latter. There is a key difference between the two types of proscribed exchanges: repugnancy and distastefulness. The repugnancy of a transaction is determined by a single factor: tastes (preferences). The distastefulness of a transaction is determined by two factors: the true intention of the actor and the context of the transaction. We characterize tastefulness/distastefulness as a judgment: does the context of the transaction, which expresses "declared intention, " match the "true intention" of the actor? We identify four different kinds of intentions and their matching contexts of exchange. This allows us to classify four different kinds of tasteful transactions, i.e. when true intentions correspond to declared ones—i.e., to their context. It also allows us to classify twelve different kinds of distasteful transactions.